Impact of pacing output and cycle length on qrs morphology in ablation of premature ventricular contractions (PACE-MAP-Trial). (19th May 2022) - Van Den Bruck, J-H; Woermann, J; Sultan, A; Filipovic, K; Scheurlen, C; Erlhoefer, S; Arica, Z; Dittrich, S; Schipper, J; Steven, D; Lueker, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pace mapping is an established technique to localize the origin of premature ventricular contractions (PVC). The QRS morphology induced by endocardial pacing is compared with a previously recorded template of the target arrhythmia. Based upon historic in-vitro models pacing at the arrhythmia's coupling interval (CI) and stimulation threshold has become the gold standard in pace mapping. Purpose: There is a paucity of data supporting pacing at the CI and stimulation threshold as the gold standard for pace mapping. In this prospective study, we sought to assess systematically the impact of variations of pacing output and cycle length on the resulting QRS morphology during pace mapping in the context of PVC ablation (NCT05061498). Methods: All patients undergoing ablation of idiopathic PVC were prospectively enrolled in this study. Pace mapping was performed using four different parameter settings: (1) A predefined fixed burst at maximum output (10V/2ms), (2) fixed burst at stimulation threshold, (3) coupling interval at maximum output and (4) coupling interval at stimulation threshold. Pacing cycle length (PCL) of the fixed burst was defined as follows: for a CI ≤450ms = PCL of CI+100ms and for a CI ≥450 = PCL of CI-100ms. Using an automated waveform comparison algorithm, the resulting QRS complexes were matched with the clinical PVC, and with the gold standard. For every parameter setting the mean of the matching percentage of three QRS complexes entered the analysis. Results: We report data of the first 22 consecutive patients (53±15 years, 64% female) enrolled in this ongoing study between May and November 2021. The pacing protocols were performed at 39 different sites: 5/39 epicardially via great cardiac vein, 15/39 in the RVOT 12/39 and 7/22 in the left ventricular cavity. When comparing the QRS morphologies resulting from the four different pace mapping settings with the clinical PVC, the univariate analysis revealed no difference between groups (p=0.9). Furthermore, there was no difference comparing the paced QRS morphologies at different output and cycle length to the gold standard of threshold pacing at coupling interval (p=0.9). Conclusion: Variations of pacing output and stimulation cycle length during pace mapping does not affect QRS morphology during PVC ablation. Applying a modern automated waveform comparison tool, no advantage was observed when comparing with the gold standard. It is therefore reasonable to assume, that pace mapping can be performed using an easily applicable setting of a fixed burst at maximum pacing output.